Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12943-016-0570-y
|View full text |Cite|
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor/cytochrome P450 1A1 pathway mediates breast cancer stem cells expansion through PTEN inhibition and β-Catenin and Akt activation

Abstract: BackgroundBreast cancer stem cells (CSCs) are small sub-type of the whole cancer cells that drive tumor initiation, progression and metastasis. Recent studies have demonstrated a role for the aryl hydrocarbon receptor (AhR)/cytochrome P4501A1 pathway in CSCs expansion. However, the exact molecular mechanisms remain unclear.MethodsThe current study was designed to a) determine the effect of AhR activation and inhibition on breast CSCs development, maintenance, self-renewal, and chemoresistance at the in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 47 publications
2
99
0
Order By: Relevance
“…TCDD promotes cell proliferation such as breast cancer stem cells (40) and hepatic stem cells (29) via AHR-dependent pathway, indicating that AHR may be a potential target for cancer chemotherapy (41). AHR is involved in various aspects of cardiovascular homeostasis and diseases, including cardiomyocyte differentiation in embryonic development (42), angiotensin II release from endothelial cells in hypertension (43), and vascular remodeling in placenta (44).…”
Section: Discussionmentioning
confidence: 99%
“…TCDD promotes cell proliferation such as breast cancer stem cells (40) and hepatic stem cells (29) via AHR-dependent pathway, indicating that AHR may be a potential target for cancer chemotherapy (41). AHR is involved in various aspects of cardiovascular homeostasis and diseases, including cardiomyocyte differentiation in embryonic development (42), angiotensin II release from endothelial cells in hypertension (43), and vascular remodeling in placenta (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to seasonal dust-storms, inhalation of chemicals, pollution of air by electric generators across urban suburbs and carcinogens which may increase the level of CYP1A1 expression/mutation in the target tissues. Activation via the aryl hydrocarbon receptor (AhR), by affecting cell signaling pathways, might reflect the role of the AhR in tumor progression ( 41 , 42 ). The mechanism of interaction between AhR and CYP1A1 or CYP2, where both are involved in the metabolism of estrogen which may lead to alteration in steroid levels modulating bioactivation of therapeutic agents and xenobiotics and elevating the risk of breast cancer in smoking women.…”
Section: Discussionmentioning
confidence: 99%
“…Among the signalling pathways that regulate cell metabolism, activated PI3K/Akt leads to enhanced glucose uptake and glycolysis [25]. A recent report shows that AhR/CYP1A1 signalling pathway controls human breast cancer stem cell development, maintenance, and self-renewal through β-Catenin and PTEN/Akt mechanisms [27]. We also showed that AhR activation after B[a]P exposure, leads to p53 activation involved in the mitochondrial activity of hexokinase II [28].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 66%